Arctic Investment Protocol - Blom, Anders; Brady, Anne-Marie; Brigham, Lawson; Conley, Heather; Daly, Michael; Hamilton, Neil; Hansen, Rúni M.; Harper, Susan; Henriksen, Sturla; Kamikawa, Yoko; Kortunov, Andrei V.; Minerd, Scott; et al. (World Economic Forum, 2015)
Guidelines for responsible investment in the arctic